The future of environmental social work: Looking to community initiatives for models of prevention. Issue 3 (2nd October 2019) - Teixeira, Samantha; Mathias, John; Krings, Amy
ABSTRACT: Social work responses to environmental degradation have sought to mitigate harm that has already occurred and create strategies to respond or adapt to environmental hazards. Despite a good deal of literature suggesting the promise of prevention-focused models, social workers have less frequently considered prevention models to address environmental issues. In this manuscript, we consider how communities engaged in environmentally-based prevention work might inform the development of ecosocial work practice. We describe how a prevention-focused agenda, in partnership with communities, can be a promising avenue for ecosocial work practice to address the root causes of environmental degradation and its social impacts.